Youth and Sports Forums’ Administration and Their Relationship with Baghdad’s Youth and Sport Directorates Forum Organizational Culture from Workers’ Point of View - Fadel, Ghassan Abbas; Kadem, Muhammad Jawad (Journal of Physical Education, 2021)
The study aimed at identifying youth and sport forums from planning and leadership point of view and their relation with organizational culture. The researchers used the descriptive method on (140) worker in Baghdad youth and sport forums. A scale was designed for measuring planning and leadership in youth and sport forums as well as designing a scale for measuring organizational culture. After the application of the main experiment, the results showed that both youth and sport forum administration scale and organizational culture scale are appropriate to the study community. Finally the researchers recommended using these scales by workers in youth and sport forums and involving administration mangers in periodical training courses and keeping them updated with all modern administrative styles and organizational cultures.